Prevalence of Human Papillomavirus (HPV) Genotypes in Cervicovaginal Secretions of Human Immunodeficiency Virus (HIV) Positive Indian Women and Correlation With Clinico-Virological Parameters - Lall, Mahima; Dar, Lalit; Bhatla, Neerja; Kumar, Pankaj; Choudhary, Aashish; Mathur, Sandeep R.; Gupta, Rajiv M. (Frontiers in Reproductive Health, 2021)
Both human papillomavirus (HPV) and the human immunodeficiency virus (HIV) are sexually transmitted. High-risk (HR) HPV types are a causal factor in cervical cancer. Persistent HPV infection in this subset of immunocompromised women results in faster disease progression. The study determined prevalence of HPV genotypes in cervicovaginal secretions of HIV seropositive women and correlation with CD4 counts and cytology. Method: One hundred, HIV-positive women 18 years of age and above were enrolled in this cross-sectional study following approval by the ethical committee. HPV genotyping was carried out with PCR amplification followed by reverse hybridization by line probe assay (LPA) using the INNOLiPA HPV Genotyping Extra kit, (Fujirebio,Belgium). Quantitation of HPV-16 and -18 viral loads (VLs) was done by real time PCR. Results of Pap smear cytology were correlated with CD4 counts and HPV-16 and -18 viral loads. Results: Mean age of the subjects was 34.9 years ± 7.2 years (median 33.0 years, range 24-60 years). HPV was detected in 62/93 (66.6%) of the samples. HPV-16 was the commonest genotype detected in 26 (27.9%) of all samples and in 41.9% of HPV positive samples. Pap smear cytology was reported for 93 women included in the study. Women who had a normal cytology were reported as negative for intraepithelial malignancy or lesion (NILM) (n=62) (71.36%), two women had a high-grade squamous intraepithelial lesion (HSIL), low-grade squamous intraepithelial lesion (LSIL) (n=11), atypical squamous cells of undetermined significance (ASCUS) (n=12). The median CD4 count was 363/cu.mm (range 39-787) in HPV positive women compared to 423/cu.mm (range 141-996) in those negative. Thirteen (13) of these 20 samples (65%), were positive by real-time PCR. The normalized HPV-16 VL ranged between 18 to 240000 copies/cell. and normalized HPV-18 VL ranged between 24 - 60000 copies per cell. Conclusions:Studies are required to determine the predictive role of HR HPV genotypes, in significant copy numbers especially in HIV seropositive women. It would be clinically relevant if the HPV VLs, cervical cytology, CD4 counts are considered into cervical cancer screening programs for triage and follow up of these women.